Feasibility analysis of a prevention programme for patients with early chronic disease using A mathematical model. Issue 2 (3rd April 2022) - Meng, Fanwen; Tan, Aidan Lyanzhiang; Heng, Bee Hoon; Leow, Melvin Khee Shing; Kannapiran, Palvannan
ABSTRACT: The increasing prevalence of the chronic disease is of considerable concern to health-care organisations. Prevention programmes to patients with early chronic disease have the potential to improve individual health and quality of life through disease avoidance or delay and to save the medical cost of the health care system. Due to the limited budget in healthcare this study seeks to analyse the feasibility of a programme prior to implementation. A mathematical model is developed to determine incidence reduction rate at which the underlying cost break-even can be achieved; consequently, the programme would be feasible. We show the existence and uniqueness of the underlying incidence reduction and establish the feasibility frontier concerning the trade-offs between intervention effective period and incidence reduction rate. We use a diabetes prevention programme to demonstrate the efficiency and advantage of the model. The proposed model would inform decision-makers scientific principles in determining an intervention for implementation.